Angiotensin II increases coronary fibrosis, cardiac hypertrophy and the incidence of myocardial infarctions in ApoE-/-Fbn1C1039G+/- mice. Issue 4 (1st August 2016) - Roth, Lynn; Schrijvers, Dorien M.; Martinet, Wim; De Meyer, Guido R.Y.
Abstract : Objective Apolipoprotein E deficient mice (ApoE -/- ) with a heterozygous mutation in the fibrillin-1 gene (Fbn1 C1039G+/- ) develop increased arterial stiffness, accelerated plaque progression, spontaneous plaque ruptures, myocardial infarction (MI) and sudden death. In the present study we used angiotensin II (Ang II) infusion to assess the responsiveness of the ApoE -/- Fbn1 C1039G+/- mouse model to risk factors of atherosclerosis, such as high blood pressure and inflammation. Methods and results Osmotic minipumps filled with phosphate buffered saline or Ang II (1, 000 ng/kg/day) were implanted in ApoE -/- Fbn1 C1039G+/- mice at week 14 of Western diet (WD). After 4 weeks of therapy, we were not able to detect an increase in blood pressure, but we observed severe aneurysms in both the thoracic and abdominal aorta of Ang II treated mice. Plaque size and composition in the proximal ascending aorta was not altered. Nevertheless, coronary fibrosis, cardiac hypertrophy and a 6-fold increase in the occurrence of MI in Ang II-treated mice was observed, which did not result in a higher mortality. Conclusion The study showed that Ang II treatment in ApoE -/- Fbn1 C1039G+/- mice increased cardiac hypertrophy, coronary fibrosis and the incidence of MI, without affecting blood pressure, plaque vulnerability and survival.